2013
DOI: 10.1108/00021461311321294
|View full text |Cite
|
Sign up to set email alerts
|

Farmland rental markets: trends in contract type, rates, and risk

Abstract: Purpose -This article aims to explore recent trends in farmland rental markets using data for the state of Illinois. Trends in the types of rental agreements used and the relationship between the rental rate for those contracts, land values, crop revenues, production costs, and farm returns are examined. Design/methodology/approach -Data from various sources and at different levels of aggregation for the state of Illinois are used to provide illustrations of historical trends in farmland rental agreements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…Across the Midwest, the majority of farmland is controlled under rental agreements, which have been increasingly of the fixed cash rent-type, although no such data exist to assess if Ohio has similar trends. 13 Paulson and Schnitkey (2013) note that since 2005, fixed-cash rents became the preferable option of operated farmland in Illinois, with around 40% of all operated land (as opposed to share rent agreement or owner-operated land). In their study, cash rental agreements represented about 25% of operated land in 1997 and have had a steady increase in operated acreage across the state.…”
Section: Datamentioning
confidence: 99%
“…Across the Midwest, the majority of farmland is controlled under rental agreements, which have been increasingly of the fixed cash rent-type, although no such data exist to assess if Ohio has similar trends. 13 Paulson and Schnitkey (2013) note that since 2005, fixed-cash rents became the preferable option of operated farmland in Illinois, with around 40% of all operated land (as opposed to share rent agreement or owner-operated land). In their study, cash rental agreements represented about 25% of operated land in 1997 and have had a steady increase in operated acreage across the state.…”
Section: Datamentioning
confidence: 99%
“…The decision to rent land is usually made on the basis of short-to medium-term considerations, without speculation on an increase in the value of the land [13]. Opposed to expansion via additional land ownership renting additional farmland has also been shown to provide a lower risk opportunity for growth, resulting in a greater ability to repay farm debt [14,15]. Additionally, the higher the transaction costs on the land sale market, the more important land rental markets are for farmers in comparison [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies discussed the impact of risk on farmland leasing. For example, Paulson and Schnitkey [14] examined the relationship between contract type, rental rates, crop revenues and risk and found that the tenure position of a farm operation has a significant effect on risk exposure due to the price volatility. Yang et al [23] analyzed the effect of landowners' risk and time preferences and land quality on the equilibrium terms of contracts (land-leasing contract, fixed-price contract and revenue-sharing contract) with the purpose of net benefit maximization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al [23] analyzed the effect of landowners' risk and time preferences and land quality on the equilibrium terms of contracts (land-leasing contract, fixed-price contract and revenue-sharing contract) with the purpose of net benefit maximization. However, recent studies mainly considered the contract types' determination [14,16,17], and few of them especially paid close attention to the decision of the term of a farmland lease contract.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation